2012
DOI: 10.4155/bio.12.3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Triple Quadrupole And High-Resolution Tof-Ms For Quantification of Peptides

Abstract: Based on sensitivity, the newest generation triple quadrupole MS systems are still the preferred technology for quantification of peptides. Since the sensitivity difference between triple quadrupole instruments and the new-generation high-resolution TOF-MS instruments is minor, the latter offer a useful alternative whenever additional selectivity is preferred or the use of a generic approach not requiring method optimization is advantageous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…This article, and others, also discussed the even greater challenges of determining low abundance peptides, where the need for high specificity and sensitivity represents a significant opportunity for HRMS in bioanalysis [59]. Similar comments were also made by Lieve Dillen et al who concluded that modern HRMS platforms are continuing to bridge the sensitivity gap and offer unique strengths versus tandem quadrupole systems [65]. Such publications point out that the area of greatest current interest for quantitative analysis is for peptides and biological therapeutics for which assays are challenged using MRM approaches from high matrix interference and poor fragmentation efficiency [66,67].…”
Section: Lc-hrms In Bioanalysismentioning
confidence: 62%
“…This article, and others, also discussed the even greater challenges of determining low abundance peptides, where the need for high specificity and sensitivity represents a significant opportunity for HRMS in bioanalysis [59]. Similar comments were also made by Lieve Dillen et al who concluded that modern HRMS platforms are continuing to bridge the sensitivity gap and offer unique strengths versus tandem quadrupole systems [65]. Such publications point out that the area of greatest current interest for quantitative analysis is for peptides and biological therapeutics for which assays are challenged using MRM approaches from high matrix interference and poor fragmentation efficiency [66,67].…”
Section: Lc-hrms In Bioanalysismentioning
confidence: 62%
“…They determined that sensitivity levels were comparable and in some cases better with the HRMS instrument when utilizing the collision cell [33]. While the choice of which MS platform to use for the quantitation of peptides will continue to be debated, the final decision should be based on cost, desired sensitivity, timelines, and the purpose of the assay [34,35]. Another challenge for the quantitation of peptides is that ESI often generates peptide ions distributed across multiple charge states.…”
Section: Quantitation Of Peptidesmentioning
confidence: 98%
“…These analyzers generally fit into two categories: high-resolution and low-resolution. While high-resolution instruments are most commonly employed in untargeted analyses [33], low-resolution instruments, specifically the triple quadrupole (QQQ), is by far, the most common analyzer employed for targeted quantitation and can be used in multiple configurations including full scan, SIM and MRM [34] and most recently, MRM 3 [35]. A MRM based QQQ method and workflow ( Fig.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%